Hindi DJ sampler. - Warner Music Malaysia (Kuala Lumpur : Warner Music Malaysia, 1999)
Contains songs from Hindi movies Mann and Hello Brother.
CD 1 : Tinak Tin Tana (Mann) -- Mera Mann (Mann) -- Nasha Yeh Pyar Ka (Mann) -- Hello Brother (Hello Brother) -- Hata Sawan Ki Ghta (Hello Brother) -- Teri Chunnariya (Hello Brother).
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Songs, Hindi